2022
DOI: 10.1111/cpf.12750
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial perfusion by CMR coronary sinus flow shows sex differences and lowered perfusion at stress in patients with suspected microvascular angina

Abstract: Background Patients with chest pain may have normal coronary arteries and suffer from microvascular angina (MVA). The aim of this study was to determine if patients with suspected MVA have lower global myocardial perfusion (global MP) during adenosine stress compared with healthy controls and coronary artery disease (CAD) patients and to determine if there are sex differences in global MP. Methods Twenty‐three patients with suspected MVA (66 ± 11 years), 19 CAD patients (69 ± 5 years) with stress‐induced ischa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…The sex differences in myocardial perfusion min at stress shown in the current study support findings in previous studies using PET (Danad et al, 2014) and CMR (Gyllenhammar et al, 2022;Nickander et al, 2020) in both healthy subjects and patients. It has been shown…”
Section: Sex Differences In Myocardial Perfusionsupporting
confidence: 91%
See 1 more Smart Citation
“…The sex differences in myocardial perfusion min at stress shown in the current study support findings in previous studies using PET (Danad et al, 2014) and CMR (Gyllenhammar et al, 2022;Nickander et al, 2020) in both healthy subjects and patients. It has been shown…”
Section: Sex Differences In Myocardial Perfusionsupporting
confidence: 91%
“…In the current study, it was shown that females referred for coronary angiography due to angina have a significantly higher myocardial perfusion at stress compared to males in myocardium supplied with coronary arteries with <50% stenosis, which might be explained by differences in the presence of microvascular disease or diffuse coronary atherosclerosis. This difference has previously also been shown in healthy volunteers (Gyllenhammar et al, 2022; Nickander et al, 2020). Furthermore, females often present with nonsignificant coronary artery stenosis on coronary angiographies, more so than males (Shaw, Berman, et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, a total of 67 independent populations were included. Among the 47 studies, 22 were from Japan [ 19 21 , 23 37 , 42 , 44 , 45 , 47 ], eight from the United States [ 7 , 14 , 22 , 40 , 41 , 48 , 51 , 55 ], five from Sweden [ 12 , 16 , 17 , 53 , 54 ], three from Germany and Sweden [ 11 , 15 , 46 ], two from Finland [ 38 , 39 ], and one each from Australia [ 18 ], France [ 43 ], Italy [ 9 ], Norway [ 13 ], Turkey [ 10 ], the United Kingdom [ 49 ], Switzerland [ 7 ], and the Netherlands [ 50 ]. Year of publication ranged from 1992 to 2022.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies [ 10 , 12 , 40 , 48 ], the VENC during stress was 200 cm/s. In the study by Gyllenhammar et al [ 16 ], the VENC was 120 cm/s. According to Moro et al [ 43 ], the VENC was 150 cm/s.…”
Section: Resultsmentioning
confidence: 99%